2019
DOI: 10.3389/fpubh.2019.00335
|View full text |Cite
|
Sign up to set email alerts
|

The Arts and Tools for Using Routine Health Data to Establish HIV High Burden Areas: The Pilot Case of KwaZulu-Natal South Africa

Abstract: Background: To optimally allocate limited health resources in responding to the HIV epidemic, South Africa has undertaken to generate local epidemiological profiles identifying high disease burden areas. Central to achieving this, is the need for readily available quality health data linked to both large and small geographic areas. South Africa has relied on national population-based surveys: the Household HIV Survey and the National Antenatal Sentinel HIV and Syphilis Prevalence Survey (ANC) amongst others fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Study results found geographic variation between urban and rural districts and population density that may account for the difference in the number of tests conducted per 100 000. The effect of area population size between urban and rural areas as implied by Wabiri et al ( 2019 ), may account for the discrepancy in the rate of HIV tests being conducted per 100 000 population and the HIV testing rates (Wabiri et al, 2019 ). Therefore, in order to achieve ideal HIV testing coverage, it is necessary to provide more equitable geographic distribution of HIV testing services.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Study results found geographic variation between urban and rural districts and population density that may account for the difference in the number of tests conducted per 100 000. The effect of area population size between urban and rural areas as implied by Wabiri et al ( 2019 ), may account for the discrepancy in the rate of HIV tests being conducted per 100 000 population and the HIV testing rates (Wabiri et al, 2019 ). Therefore, in order to achieve ideal HIV testing coverage, it is necessary to provide more equitable geographic distribution of HIV testing services.…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of South Africa’s National Strategic Plan (NSP) for HIV, TB and STIs 2017–2022 is to address the burden of HIV in the country through the use of strategic information such as routinely collected data for monitoring the progress towards achieving the United Nations (UN) Sustainable Development Goals (SDGs) as well as to determine the utilisation of services (National Department of Health, 2016c ). There is also a need to evaluate the impact of interventions on programmes that are implemented in response to the burden of disease and to ensure that interventions are focused on high-burden areas with populations that are most at risk (Wabiri, Naidoo, Mungai, Samuel, & Ngwenya, 2019 ). Routinely collected data from public health facilities are housed on the District Health Information System (DHIS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions adapted to the sub-state or district level can be especially effective. Studies in Botswana [10], Kenya [6], Lesotho [11], Malawi [12], Rwanda [13], and South Africa [14] indicate that geographic targeting could increase the impact of prevention interventions, with some studies identifying "hotspots" for greater prioritization in geographic areas as small as the community level [15]. Despite the recent evidence that shows the usefulness of geospatial estimates for targeted intervention planning and policymaking [16,17], there are few examples describing the derivation and practical application of sub-state geospatial estimates for targeted intervention planning.…”
Section: Introductionmentioning
confidence: 99%